СOMPARATIVE ASSESSMENT OF DIAGNOSTIC REAGENTS FROM SYNTHETIC AND ERYTHROCYTE SORBENTS FOR THE DETERMINATION OF LYMPHOCYTES WITH RECEPTORS FOR BRUCELLA LIPOPOLYSACCHARIDES - Karalnik , B.V.; Denisova , T.G.; Omarova , M.N.; Zhunussova , G.B.; Tugambayev , T.I.; Zakaryan , S.B.; Fedosov , Y.S. (Eurasian Journal of Applied Biotechnology, 2016)
The aim of this study was to develop immunologic reagents from a synthetic sorbent for early brucellosis diagnostics and compare them with previously developed erythrocyte immunologic reagents by using animal immunization experiments and examination of patients. Rabbits; veterinary brucellosis vaccines for sheep and cattle; lipopolysaccharides (LPS) of different species of Brucella and Yersinia chemically activated (with -NH2or –COOH groups) with polystyrene beads(diameter,2 µm) and tagged or not tagged with a fluorochrome (natriumisothiocyanate); previously developed Brucella erythrocyte immunologic reagent for revealing lymphocytes with receptors for the antigens; and mononuclear fractions of rabbits and patients suspected to have brucellosis were used. Methods of adhesion of cells/corpuscles and their blocking with LPS and statistical comparisons were used. A Brucella immunologic reagent was developed from the synthetic sorbent for determining LfRLPS specificity. Advantages of the developed immunologic reagent were as follows: absence of non-specific adhesion due to binding of the sorbent rather than LPS and higher accuracy of determination of LfR; non-obligation of parallel determination of sorbent binding per se by lymphocytes; and simplification and decrease of spending time for the LfR count. Features of the sorbent did not influence the detection of LfR specific to taxonomically close bacteria. The results substantiate the expediency of use of the immunologic reagent from a synthetic sorbentfor the determination of LfR.